مستوى انتشار العنف ضد الزوجة وأثره على جودة العلاقة الزوجية لدى عينة من الزوجات السعوديات بمدينة جدة - الغامدي، نوال غرم الله; خليفة، فاطمة خليفة السيد (كلية الإمارات للعلوم التربوية, 2021)
The aim of this study was to identify the prevalence of violence against the wife and the prevalence of quality of marital relationship among a sample of Saudi wives in Jeddah, also evaluate the relationship between violence against the wife and quality of the marital relationship, also identify the difference in study variables led to the difference of family's economic level, This study sample consisted of Saudi wives in Jeddah (N= 380) they were evaluated using violence against the wife Scale, and quality of marital relationship Scale, The descriptive approach was used, both associative and comparative, The results showed there is a medium level of violence against the wife, and a low level of the quality of the marital relationship, the results also found an inverse correlation between violence against the wife and the quality of the marital relationship, and there are differences in violence against the wife due to the economic level of the family in the direction of the low level, and there are differences in the quality of the marital relationship due to the economic level of the family in the direction of the high level. The study recommended activating the role of social institutions in protecting the wife from the violent behavior of some husbands, enforcement psychological care programs for abused wives, following up on the psychological effects of violence, and holding awareness workshops for husbands who suffer from poor quality marital relations.
هدفت الدراسة الحالية إلى الكشف عن مستوى انتشار العنف ضد الزوجة، ومستوى جودة العلاقة الزوجية لدى عينة من الزوجات السعوديات بمدينة جدة، كما هدفت الدراسة إلى التحقق من العلاقة بين العنف ضد الزوجة وجودة العلاقة الزوجية، والتعرف على الفروق في متغيري الدراسة والتي تعزى إلى اختلاف المستوى الاقتصادي للأسرة، واشتملت الدراسة على (380) من الزوجات السعوديات تراوحت أعمارهن بين (25- 55) عاماً، بمتوسط عمر قدره 36.80 عاماً وانحراف معياري قدره 7.16، وطبق عليهن مقياس العنف ضد الزوجة، ومقياس جودة العلاقة الزوجية، واستخدم المنهج الوصفي ذو التصميم الارتباطي والمقارن. أظهرت النتائج وجود مستوى متوسط من العنف ضد الزوجة، ومستوى منخفض من جودة العلاقة الزوجية، كما توصلت النتائج إلى وجود علاقة ارتباطية عكسية بين العنف ضد الزوجة وجودة العلاقة الزوجية، ووجود فروق في العنف ضد الزوجة يعزى للمستوى الاقتصادي للأسرة في اتجاه المستوى المنخفض، كما يوجد فروق في جودة العلاقة الزوجية تعزى للمستوى الاقتصادي للأسرة في اتجاه المستوى المرتفع. وتوصي الدراسة بتفعيل دور المؤسسات الاجتماعية في حماية الزوجة من التصرفات العنيفة لبعض الأزواج، وتنفيذ برامج رعاية نفسية للزوجات المعنفات ومتابعة الآثار النفسية المترتبة على العنف، وعقد ورش عمل توعوية للأزواج الذين يعانون ضعف في جودة العلاقات الزوجية.
Keywords: المؤسسات الاجتماعية -- العلاقات الزوجية -- المرآة السعودية -- التميز العنصري